ACC/AHA pocket guidelines for evaluation and management of chronic heart failure in the adult : report of the American College of Cardiology/American Heart Association task force on practice guidelines (committee to revise the 1995 guidelines for the evaluation and management of heart failure) - Hunt, Sharon A.; Baker, David W.; Chin, Marshall H.; Cinquegrani, Michael P.; Feldman, Arthur M.; Francis, Gary S.; Ganiats, Theodore G.; Goldstein, Sidney; Gregoratos, Gabriel; Jessup, Mariell L.; Noble, R. Joseph; Packer, Milton; et al. (s.n., 2002)
The writing committee decided to take a new approach to the classification of HF that emphasized both the evolution and progression of the disease. In doing so, we identified 4 stages of HF. Stage A identifies the patient who is at high risk for developing HF but has no structural disorder of the heart; stage B refers to a patient with a structural disorder of the heart but who has never developed symptoms of HF; stage C denotes the patient with past or current symptoms of HF associated with underlying structural heart disease; and stage D designates the patient with end-stage disease who requires specialized treatment strategies such as mechanical circulatory support, continuous inotropic infusions, cardiac transplantation, or hospice care. Only the latter 2 stages, of course, qualify for the traditional clinical diagnosis of HF for diagnostic or coding purposes. This classification recognizes that there are established risk factors and structural prerequisites for the development of HF and that therapeutic interventions performed even before the appearance of left ventricular dysfunction or symptoms can reduce the morbidity and mortality of HF.